EFEKTIVITAS MODEL REALISTIC MATHEMATICS EDUCATION (RME) DENGAN STRATEGI SCAFFOLDING DALAM MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Kiky Ardhianti; Bambang Agus Sulistyono; Samijo (Afore : Jurnal Pendidikan Matematika, 2026)
This study aims to determine the effect of the scaffolding-based Realistic Mathematics Education (RME) learning model on students' mathematical problem-solving abilities. This study used a quantitative approach with a quasi-experimental method through a pretest - posttest control group design. The research sample was determined using purposive sampling, namely class XI DKV 2 as the experimental class with the scaffolding-based RME learning model and class XI DKV 1 as the control class with the conventional learning model. Research data were collected through a mathematical problem-solving ability test in the form of essay questions. Data analysis techniques included descriptive statistics, independent sample t-test, and N-gain analysis. Based on the descriptive statistics results, the average post-test score for the experimental class was 76.03 and the control class had an average of 65.53. The results of the independent sample t-test showed a significant value of 0.000, indicating that sig. (2-tailed) < α=0.05. Thus, the null hypothesis (H₀) was rejected, and the alternative hypothesis (H₁) was accepted, meaning that the scaffolding-based RME learning model was effective in improving students' mathematical problem-solving skills.